Natural Oligopoly in Intermediated Markets - Thomas Gehrig (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
) and convergence to a fragmented industrial structure does not obtain as the economy grows large. In particular, we find a natural oligopoly in which in general there are three larger intermediaries of similar size and one smaller intermediary occupying niche markets. Nevertheless, as the number of islands increases, spreads shrink to zero and almost competitive allocations arise.
Keywords: D43; L11; L13; 330; intermediation; network competition; vertical product differentiation; industrual structure; natural oligopoly